Композит алмаз – карбид вольфрама для бурового инструмента - Назарчук, С.Н.; Бочечка, А.А.; Гаврилова, В.С.; Романко, Л.А.; Ткач, В.Н.; Свешников, И.А.; Заболотный, С.Д. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Composite diamond-tungsten carbide based on diamond powders of different dispersity was created. The optimal number of large diamond powder in the composite was determined. The structure of the composite, its physical-mechanical and operational properties are investigated.